Junior High School Students’ Writing Mastery on English Decriptive and Recount Texts - Febri Rama Suci; Maratus Shalihah; Darmayenti Darmayenti (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This paper aimed at finding out and describe deeply the students’ writing skill and their mastery on descriptive and recount texts. This was a descriptive research type. There were 22 students at class VIII of Junior High School 2 Sintoga as respondents of the research. Writing tests on descriptive and recount texts were used to collect the data. The data were classified into excellent, good, fair, poor, and very poor by using Jacob’ theory and calculated the data on percentage by using formula Sudijono. It was found that the students got fair skill for both mean score of students based on component writing descriptive and recount texts (57.18 and 58.1). For the each component of genres, they got lower score on content, organization of text, vocabulary, and language use. On descriptive text, there were 16 students’ mastery on generic structure for beginning stage and 8 students for developing stage. Meanwhile, for generic structure of recount text 10 students were mastery on generic structure for beginning stage, 11 students for developing stage, and 1 student for consolidating stage. Most of students made the mistakes in orientation and events. Some students who did not give the information of the place (where), time (where), and the reason (why) clearly in the orientation. In the events, some students wrote their experience unchronologicaly. It is concluded that the students’ mastery on writing descriptive and recount texts are fair category. It implies that the students should improve their writing skill through building writing habit and English teacher should be able to find out effective techniques and strategies in teaching writing skills.